2019
DOI: 10.1016/j.jmps.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Buckling initiation in layered hydrogels during transient swelling

Abstract: Subjected to compressive stresses, soft polymers with stiffness gradients can display various buckling patterns. These compressive stresses can have different origins, like mechanical forces, temperature changes, or, for hydrogel materials, osmotic swelling. Here, we focus on the influence of the transient nature of osmotic swelling on the initiation of buckling in confined layered hydrogel structures. A constitutive model for transient hydrogel swelling is outlined and implemented as a user-subroutine for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…We believe, the buckling conformation is achieved due to the influence of high transient swelling forces with swelling mismatch occurring in one of the functional blocks. [ 40 ] When more than two patterns were involved, complex surface convex and concave buckling can be observed that transients over time with changing diffusion coefficients and ionic equilibrium, as detailed in the Supporting Information and Figure S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…We believe, the buckling conformation is achieved due to the influence of high transient swelling forces with swelling mismatch occurring in one of the functional blocks. [ 40 ] When more than two patterns were involved, complex surface convex and concave buckling can be observed that transients over time with changing diffusion coefficients and ionic equilibrium, as detailed in the Supporting Information and Figure S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The successful design of hydrogel systems relies on predictive methods for the stability of swelling gels providing sound stability diagrams. Previous computational studies on the instability of gels have made use of two main methods, finite element (FE) simulations [16][17][18][19][20][21] or perturbation analysis (PA) [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…FE simulations have successfully been applied to study geometrical instability of transiently swelling gels in a few recent studies [19][20][21]. This method excels in its applicability to general geometries and loading conditions, and use of the method has demonstrated that the swelling kinetics can alter both the level of swelling and the wavelength of the surface pattern at the onset of instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These provide improved hyperelastic models that describe the equilibrium swelling behavior of hydrogels [ 16 , 17 , 18 , 19 ]. More complex time-dependent models can also describe the transient nature of swelling [ 20 , 21 , 22 , 23 , 24 , 25 ]. Nevertheless, most of the work dealing with the modeling of hydrogel swelling are qualitative evaluations of the model’s capability of capturing important features of the swelling process.…”
Section: Introductionmentioning
confidence: 99%